2015
DOI: 10.1016/j.sbspro.2015.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Apology Strategy among Male and Female Kurdish Bilinguals at Ilam

Abstract: The present study was aimed at exploring and describing apology strategies among Kurdish bilinguals in Ilam, Iran. It attempts to systematize the various strategies used for the purpose of apologizing from the pragmatic point of view. The current study involves 80 subjects of Kurdish bilinguals in Ilam, consisting of 40 male and 40 female subjects. The subjects were chosen randomly to participate in this study. The data of this study was collected through a controlled elicitation method based on a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Apology is a speech act to show recognition of the fact that violation of a social norm has taken place. It is an act used to express speakers' mental and emotional state or any sincerity condition of the propositional content (Searle, 1976), functioning to reestablish the social harmony, trust and conflict resolution (Goffman, 1971;Olshtain & Cohen, 1983), to give a recompense for the misdemeanor (Blum-Kulka & Olshtain, 1984), and to retain a good connection between the apologizer and the recipient (Brown & Levinson, 1978). Like other common speech acts, apology is subject to cultural and linguistic differences where speakers of a particular language or members of a particular culture may have their own unique realization of the speech act of apology.…”
Section: Apologymentioning
confidence: 99%
See 1 more Smart Citation
“…Apology is a speech act to show recognition of the fact that violation of a social norm has taken place. It is an act used to express speakers' mental and emotional state or any sincerity condition of the propositional content (Searle, 1976), functioning to reestablish the social harmony, trust and conflict resolution (Goffman, 1971;Olshtain & Cohen, 1983), to give a recompense for the misdemeanor (Blum-Kulka & Olshtain, 1984), and to retain a good connection between the apologizer and the recipient (Brown & Levinson, 1978). Like other common speech acts, apology is subject to cultural and linguistic differences where speakers of a particular language or members of a particular culture may have their own unique realization of the speech act of apology.…”
Section: Apologymentioning
confidence: 99%
“…In relation to apology in English, a number of studies accord with Qorina's finding that learners of English as a Second Language (ESL) or English as a Foreign Language (EFL) apologize in the norm of their L1 culture (Olshtain & Cohen, 1983;Suszczynska, 1999;Thijittang, 2010;Qorina, 2012;Parsa, H., & Mohd Jan, 2015). Regarding gender, previous studies showed that gender (sex) does not have a significant impact on the use of apology strategies (Saleem, Azam & Saleem, 2014;Hassan, 2014;Ghanbari et al, 2015;Ali Harb, 2015). Concerning proficiency level, many believe that higher proficiency learners have better performance in apology.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of apology in real life conversation has been studied by several researchers with various focuses. The cross cultural studies compare an apology in English and other languages (see for example, Yi, 2006;Chamani & Zareipur, 2010;Aydin, 2013), single language (Dementer, 2000;Shariati & Chamani, 2010;Banikalef, et al, 2015), and across gender (Juhana, 2011;Fitriani, 2012;Chunlin, 2013;Ghanbari, et al, 2014;Majeed & Janjua, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So, he hypothesized that there would be more differences than similarities between males and females in their use of apology strategies due to gender-related issues and in light of previously conducted research that claimed more differences than similarities. The research of Ghanbari, Jamalinesari, Gowhary, and Azizfar (2015) involved 80 subjects of Kurdish bilinguals in Ilam, consisting of 40 male and 40 female subjects. They used 'Discourse Compilation Test' to test whether people in Ilam area would choice different apology strategies from western people concerning gender differences.…”
Section: Previous Studiesmentioning
confidence: 99%